Versatile Tunability of the Metal Insulator Transition in (TiO2)m/(VO2)m Superlattices. (20th September 2020) - Eres, Gyula; Lee, Shinbuhm; Nichols, John; Sohn, Changhee; Ok, Jong Mok; Mazza, Alessandro R.; Liu, Chenze; Duscher, Gerd; Lee, Ho Nyung; McNally, Daniel E.; Lu, Xingye; Radovic, Milan; et al.
Abstract: In contrast to perovskites that share only common corners of cation‐occupied octahedra, binary‐oxides in addition share edges and faces increasing the versatility for tuning the properties and functionality of reduced dimensionality systems of strongly correlated oxides. This approach for tuning the electronic structure is based on the ability of X‐ray spectroscopy methods to monitor the creation and transformation of occupied and unoccupied electronic states produced by interface coupling and lattice distortions. X‐ray diffraction reveals a new range of structural metastability in (TiO2 ) m /(VO2 ) m /TiO2 (001) superlattices with m = 1, 3, 5, 20, 40, and electrical transport measurements show metal insulator transition (MIT) behavior typically associated with presence of high oxygen vacancy concentrations. However, X‐ray absorption spectroscopy (XAS) at the Ti and V L 3, 2 ‐edge and resonant inelastic X‐ray scattering (RIXS) at the Ti and V L 3 ‐edge show no excitations characteristic of oxygen vacancy induced valance change in V and negligible intensities in Ti RIXS. The unexpected absence of oxygen vacancy related states in the X‐ray spectroscopy data suggests that superlattice fabrication is capable of suppressing oxygen vacancy formation while still affording a wide tunability range of the MIT. Achieving a wide range of MIT tunability while reducing or eliminating oxygen vacancies that are detrimental to electrical properties is highly desirable for technological applications of strongly correlated oxides. Abstract : It is reported here that superlattices consisting of alternating VO2 and TiO2 epitaxial layers provide a new metastability range with dramatically altered VO2 properties. Electrical transport and X‐ray spectroscopy measurements reveal that the superlattice properties are governed by multiple strain mechanisms and despite unexpectedly low oxygen vacancy concentration provide a wide tunability range of the VO2 metal insulator transition.